Toxicity assessment of molindone hydrochloride, a dopamine D2/D5 receptor antagonist in juvenile and adult rats. (13th June 2017) - Krishna, Gopala; Gopalakrishnan, Gopa; Goel, Saryu
Abstract: Neuroleptic drug molindone hydrochloride is a dopamine D2/D5 receptor antagonist and it is in late stage development for the treatment of impulsive aggression in children and adolescents who have attention deficient/hyperactivity disorder (ADHD). This new indication for this drug would expand the target population to include younger patients, and therefore, toxicity assessments in juvenile animals were undertaken in order to determine susceptibility differences, if any, between this age group and the adult rats. Adult rats were administered molindone by oral gavage for 13 weeks at dose levels of 0, 5, 20, or 60 mg/kg-bw/day. Juvenile rats were dosed for 8 weeks by oral gavage at dose levels of 0, 5, 25, 50, or 75 mg/kg-bw/day. Standard toxicological assessments were made using relevant study designs in consultation with FDA. Treatment-related elevation in serum cholesterol and triglycerides and decreases in glucose levels were observed in both the age groups. Organ weight changes included increases in liver, adrenal gland and seminal vesicles/prostate weights. Decreases in uterine weights were also observed in adult females exposed to the top two doses with sufficient exposure. In juveniles, sexual maturity parameters secondary to decreased body weights were observed, but, were reversed. In conclusion, the adverse effects noted in reproductive tissues of adults were attributed to hyperprolactinemia and these changes were not considered to be relevant to humans due to species differences in hormonal regulation of reproduction. On the whole, there were no remarkable differences in the toxicity profile of the drug between the two age groups.